3D printing of nerve conduits with nanoparticle-encapsulated RGFP966. (September 2019) - Xu, Xin; Tao, Jie; Wang, Shuai; Yang, Ling; Zhang, Jiumeng; Zhang, Jing; Liu, Haofan; Cheng, Hao; Xu, Jianguo; Gou, Maling; Wei, Yuquan
Graphical abstract: Highlights: A 3D-printed nerve conduit is functionalized with RGFP966 nanoparticles for local treatment. The RGFP966 promotes the remyelination of Schwann cells by PI3K–AKT–ERK pathway. The functional conduits provide favorable microenvironment to facilitate the connection of injured nerves. Abstract: Nerve conduits have great promise for bridging peripheral nerve defects that always cause disability. Currently, the clinically used nerve conduits are limited in promoting nerve regeneration, leading to the unsatisfied nerve repair efficiency. In this study, we show a 3D-printed nerve conduit with drug release for promoting nerve regeneration. This nerve conduit with designed structures as well as directional fiber-aligned inner surface is rapidly customized by a digital light processing (DLP) based continuous 3D-printing process. Meanwhile, this conduit containing polymeric nanoparticles that can sustained release RGFP966 to promote the remyelination of Schwann cells by activating PI3K–AKT–ERK signal pathway. Moreover, this nerve conduit is degradable and biocompatible. After implantation, this conduit can efficiently bridge a 10-mm rat sciatic nerve defect, which is comparable to the autograft in inducing nerve regeneration and functional recovery. This work suggests that the 3D-printed hydrogel nerve conduits with local release of RGFP966 could efficiently repair the injured nerves, which could inspire the development of future functional nerve conduits.